Optimización del método de extracción de flavonoides totales de las flores de Cordia lutea Lam. “Flor de overo” - Valdiviezo Campos, Juan Ernesto (2017)
The present report consisted in determining the optimal method of extraction of total flavonoids from the flowers of Cordia lutea Lam. "Flower of overo" collected from the district of Cormot, province of Gran Chimú. The flowers of Cordia lutea Lam were collected. "Flower of overo" in the flowering season during the month of February - March, which were subjected to cleaning, selection, stabilization, spraying, screening and storage. The extraction of extracts was then carried out by different methods of extraction. From the extracts the total flavonoids were obtained, the total flavonoids were quantified by UV-visible spectrophotometry obtaining the results expressed as Quercetin. The optimum total flavonoid yield of flowers of Cordia lutea Lam. Was extracted by Soxhlet, obtaining a percentage of 2.42 ± 0.0012%